2018
DOI: 10.1021/acsomega.8b00237
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Response in Electrospun Poly(vinylidene fluoride) Fibers Containing Fluoro-Doped Graphene Derivatives

Abstract: Herein, graphene oxide (GO) was suitably functionalized to obtain carboxylated and fluorinated GO (GOCOOH and GOF) derivatives, respectively, via the Hunsdiecker reaction. Electrospun mats of poly(vinylidene fluoride) (PVDF)/GO, PVDF/GOCOOH, and PVDF/GOF fibers were then prepared by electrospinning from well-dispersed GO derivatives. The piezoelectric coefficient ( d 33 ), as measured using piezoelectric force measurement (PFM), enhanced by more than 2 folds with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Gebrekrstos et al have determined the maximum amplitude of three nanofibers PVDF/GO, PVDF/GOCOOH, and PVDF/GOF by PFM [ 153 ]. The d33 depends on the β phase content of PVDF nanofibers and is found to be increased with the increase of the β content.…”
Section: Piezoelectric Properties On Nanofibrous Membranesmentioning
confidence: 99%
“…Gebrekrstos et al have determined the maximum amplitude of three nanofibers PVDF/GO, PVDF/GOCOOH, and PVDF/GOF by PFM [ 153 ]. The d33 depends on the β phase content of PVDF nanofibers and is found to be increased with the increase of the β content.…”
Section: Piezoelectric Properties On Nanofibrous Membranesmentioning
confidence: 99%
“…In a recent study, Bose and coworkers employed carboxylated GO (CGO) and fluorinated GO (FGO) nanofillers for further enhancing d 33 value of PVDF fibrous mats. The highest β-phase content was achieved in the PVDF/1 wt% FGO mat due to the presence of highly electronegative fluorine [148]. Consequently, PVDF/1 wt% FGO fibrous mat had a high d 33 value of 63 pm/V.…”
Section: Scaffold Fabricationmentioning
confidence: 99%
“…4d, e. Gebrekrstos et al [161] reported that the addition of fluoro-doped graphene derivatives (GO, GOF and GOOCH) during electrospinning of polyvinylidene fluoride (PVDF) offered remarkable properties including enhanced electroactive β phase, high energy density and improved piezoelectric coefficient. This drastic enhancement can be ascribed to the increase in the amount of β The combination of the sulfonation, the crosslinking, and the addition of GO enhanced the proton conductivity [42] PVA/rGO in PVDF/GO fibers and the charge separation induced by the fluorine which acts as a polarization center.…”
Section: Properties Of Electrospun Gnms Nanocompositesmentioning
confidence: 99%